Knowledge science, engineering and management 5th International Conference, KSEM 2011, Irvine, CA, USA, December 12-14, 2011. Proceedings - KSEM 2011 (2011 Irvine, Calif.); Xiong, Hui.; Lee, W. B.; SpringerLink (Online service). (Berlin New York Springer, 2011)
This book constitutes the proceedings of the 5th International Conference on Knowledge Science, Engineering and Management, KSEM 2011, held in Irvine, CA, USA, in December 2011. The 34 revised full papers presented together with 7 short papers were carefully reviewed and selected from numerous submissions.
Electronic reproduction.
Keywords: Knowledge acquisition (Expert systems) -- Congresses; Information technology -- Congresses; Knowledge management -- Congresses; Data mining -- Congresses; Decision making -- Data processing -- Congresses; Problem solving -- Data processing -- Congresses; Electronic books